Numerical Simulation Bidirectional Chaotic Synchronization of Spiegel-Moore Circuit and Its Application for Secure Communication. (March 2017) - Sanjaya, W S M; Anggraeni, D; Denya, R; Ismail, N
Abstract: Spiegel-Moore is a dynamical chaotic system which shows irregular variability in the luminosity of stars. In this paper present the performed the design and numerical simulation of the synchronization Spiegel-Moore circuit and applied to security system for communication. The initial study in this paper is to analyze the eigenvalue structures, various attractors, Bifurcation diagram, and Lyapunov exponent analysis. We have studied the dynamic behavior of the system in the case of the bidirectional coupling via a linear resistor. Both experimental and simulation results have shown that chaotic synchronization is possible. Finally, the effectiveness of the bidirectional coupling scheme between two identical Spiegel-Moore circuits in a secure communication system is presented in details. Integration of theoretical electronic circuit, the numerical simulation by using MATLAB®, as well as the implementation of circuit simulations by using Multisim® has been performed in this study.